Logic and Ethics—Hegel's Logic of Action - Nuzzo, Angelica (Revista Eletrônica Estudos Hegelianos, 2022)
This essay presents Hegel's dialectic-speculative Logic as the originally and constitutively practical movement of thinking's self-determination. While this reading implies a fundamental thesis concerning Hegel's conception of logical thinking, it is also conducive to a broader consideration of the nature of the practical sphere writ large and its philosophical thematization. This latter point is crucial when at stake is “truth” in its complex validity—truth being central not only to logical thinking and knowing but also to our embodied, worldly, historical human action. In light of this issue, the essay examines the implications of the convergence of truth and freedom in Hegel's Logic.
Keywords: Hegel; Ethics; Logic; Truth; Action